IMPLEMTASI PERMA NOMOR 02 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP TERHADAP PELAKU PENCURIAN RINGAN - Winda Yunita (Universitas Muhammadiyah Kotabumi, 2020)
This study discusses the application of Perma No. 02 of 2012 concerning adjustments to the limits of minor crimes and the amount of fines in the Criminal Code against perpetrators of minor theft. The data collection technique is carried out by the author by means of: literature study, field study, and interviews. The results of this study: 1. The application of punishment to the perpetrators of the crime of minor theft in case Number 2/Pid.C/2020/PN Bbu, namely that in this case of minor crimes, the judge's decision is only recorded in the register, that is, it is enough in the book not to make a decision. separately and the verdict of the trial is carried out on the same day or time at the same time this is so that it does not take protracted time because this minor crime is fast so that cases go to court such as traffic violations cases, 2. Basis for judges' considerations Sentencing the perpetrators of the crime of minor theft in case Number 2/Pid.C/2020/PN Bbu, was based on juridical considerations, namely based on the indictment of the public prosecutor, witness statements, statements of the defendant, evidence, while the considerations made by the public prosecutor non-juridical, namely the background of the defendant and the religion or belief held by the defendant, the physical and mental condition of the defendant and the consequences of the defendant's actions.